Low-energy ion beam diagnostics: an integrated solution - Adiguzel, A.; Cetinkaya, H.; Esen, S.; Halis, D.; Ilhan, T. B.; Kilicgedik, A.; Ogur, S.; Oz, S.; Ozbey, A.; Ozcan, V. E.; Unel, N. G. (IOP Publishing Ltd, 2024)
High gradient accelerator injectors have been widely studied throughout the world -leading accelerator facilities. The demand for high frequency cavities has led the Detector, Accelerator and instrumentation laboratory (KAHVELab) in Istanbul to deploy a four -vane Radio Frequency Quadrupole (RFQ) operating at 800 MHz to accelerate 20 keV protons to 2 MeV. The protons from the microwave discharge ion source are transversely matched to the RFQ via an optimized Low Energy Beam Transport (LEBT) line which also contains an integrated measurement station, called measurement station (MBOX). The MBOX is used to measure the proton beam's current along with pulse length duration, profile as well as the beam emittance upstream of the RFQ. It contains a number of home -built diagnostic tools: a Faraday cup, a scintillator screen and a pepper pot plate (PP). The analysis software is also locally developed and tested for the PP photo analysis. In this note, the design, construction and tests of the integrated measurement station are discussed. The results from various measurements, especially on beam profile and charge, are compared to the simulation predictions.
Keywords: Beam-line instrumentation (beam position and profile monitors; beam-intensity monitors; bunch length monitors); Accelerator Subsystems and Technologies; Ion sources (positive ions; negative ions; electron cyclotron resonance (ECR); electron beam (EBIS)); Instruments & Instrumentation